1995
DOI: 10.1107/s0108270195000217
|View full text |Cite
|
Sign up to set email alerts
|

Anhydrous Form of Carnidazole, C8H12N4O3S

Abstract: The molecular conformations of the anhydrous and hydrated forms of carnidazole {O-methyl [2-(2-methyl-5-nitro-1H-imidazol- 1-yl)ethyl]carbamothioate } differ essentially in the relative orientations of he nitroimidazole and thiocarbamate moieties. In the anhydrous form, the molecules are connected by a network of hydrogen bonds and show stacking interactions between the nitroimidazole moieties

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 4 publications
(5 reference statements)
0
10
0
Order By: Relevance
“…1) and its derivatives are known for their antiprotozoic and antibiotic properties, 2,3 and a number of crystal structures of these compounds has been solved. [4][5][6][7][8][9] Despite these studies, little is known about the thermodynamic properties that can be used for the characterization of the active pharmaceutical ingredients important not only from a regulatory point of view but also for drug development.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1) and its derivatives are known for their antiprotozoic and antibiotic properties, 2,3 and a number of crystal structures of these compounds has been solved. [4][5][6][7][8][9] Despite these studies, little is known about the thermodynamic properties that can be used for the characterization of the active pharmaceutical ingredients important not only from a regulatory point of view but also for drug development.…”
Section: Introductionmentioning
confidence: 99%
“…For carnidazole, two polymorphic anhydrous phases with different melting temperatures and enthalpies have been characterized. 5,8 This case of dimorphism was accompanied with conformational changes (with only one conformation per crystal structure), that is, a case of conformational polymorphism according to the definition proposed by Bernstein and Hagler. 10,11 For metronidazole with a shorter chain (R = CH 2 CH 2 OH), polymorphism or multiple conformations have, until now, not been observed.…”
Section: Introductionmentioning
confidence: 99%
“…The lack of any unrealistic close contacts and the presence of a realistic network of hydrogen bonds suggested that the solution could be correct. The refinement was performed by the Rietveld method15 implemented in the Fullprof suite of programs 17. The background level was modeled by a polynomial function, while systematic errors were corrected with the aid of sample displacement angular shifts.…”
Section: Methodsmentioning
confidence: 99%
“…Carnidazole exists in three different crystalline forms: anhydrous forms I and II (polymorphic forms) and a monohydrate (sometimes called pseudopolymorph by some authors). In previous works, the crystal structure of the monohydrate form14 and that of an anhydrous form of carnidazole (form I)15 have been determined by single crystal X‐ray diffraction (CSD database version 3.26, refcode CARNID and YUYPAJ , respectively) on crystals obtained by slow evaporation from mixtures of H 2 O/EtOH. Attempts to obtain crystals suitable for single crystal X‐ray diffraction experiments of form II of carnidazole have failed, making this compound a candidate to solve its crystal state structure by XRPD methods.…”
Section: Introductionmentioning
confidence: 99%
“…In previous works, the crystal structure of a monohydrate form (Blaton et al , 1979) and that of an anhydrous form of carnidazole (polymorphic form 1) have been determined by single crystal X-ray diffraction (Bernardinelli et al , 1995). These reported structures were solved and refined from single crystals obtained by slow evaporation from mixtures of H 2 O∕ Et OH.…”
Section: Introductionmentioning
confidence: 99%